1987
DOI: 10.1007/bf00205630
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiple anti-CEA immunotoxins active against human adenocarcinoma cells

Abstract: Anti-carcinoembryonic antigen (CEA) immunotoxins constructed with multiple anti-CEA antibodies (goat and baboon polyclonal, and three murine monoclonal antibodies) by covalently linking them to the A chain of ricin via a disulfide bond all function as potent and specific toxins for CEA-bearing cells, suggesting that the CEA molecule is capable of directing productive internalization of ricin A chain. The high potency of anti-CEA immunotoxins apparently makes addition of ricin B chain unnecessary for high toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Experiments in our laboratory have shown that CEA is internalized with a half-life between 10 and 16 h and thus represents a potential target for immunotoxins (24). CEA has been used previously as a target for the early development of immunotoxins (25)(26)(27). The EGF receptor (EGFR) has a strikingly faster internalization rate (ϳ30 min).…”
mentioning
confidence: 99%
“…Experiments in our laboratory have shown that CEA is internalized with a half-life between 10 and 16 h and thus represents a potential target for immunotoxins (24). CEA has been used previously as a target for the early development of immunotoxins (25)(26)(27). The EGF receptor (EGFR) has a strikingly faster internalization rate (ϳ30 min).…”
mentioning
confidence: 99%
“…It does not appear to be cytotoxic to this cell line in either a complement or ADCC assay system [22]. However, when conjugated to Ricin A chain, the baboon anti-CEA antibody is cytotoxic in vitro to human CEAbearing cell lines.…”
Section: Discussionmentioning
confidence: 98%
“…In vitro, our baboon anti-CEA antibody will bind to the human colon carcinoma Lovo cell line that produces CEA [21,22]. It does not appear to be cytotoxic to this cell line in either a complement or ADCC assay system [22].…”
Section: Discussionmentioning
confidence: 99%
“…Levin et al [12] and Byers et al [13] ob served inhibition of protein synthesis in CEA-positive cells after 46 and 64 h incuba tion, respectively, with MAb-ricin A chain immunoconjugates. However, this approach is not suitable for discriminating between MAb-mediated specific endocytosis and nonspecific pinocytosis, regardless of the point that both processes are expected to dif fer greatly in quantitative terms.…”
Section: Discussionmentioning
confidence: 99%